Nitric Oxide-cGMP Signaling in Hypertension: Current and Future Options for Pharmacotherapy. Issue 4 (October 2020) - Ataei Ataabadi, Ehsan; Golshiri, Keivan; Jüttner, Annika; Krenning, Guido; Danser, A.H. Jan; Roks, Anton J.M.
Abstract : For the treatment of systemic hypertension, pharmacological intervention in nitric oxide-cyclic guanosine monophosphate signaling is a well-explored but unexploited option. In this review, we present the identified drug targets, including oxidases, mitochondria, soluble guanylyl cyclase, phosphodiesterase 1 and 5, and protein kinase G, important compounds that modulate them, and the current status of (pre)clinical development. The mode of action of these compounds is discussed, and based upon this, the clinical opportunities. We conclude that drugs that directly target the enzymes of the nitric oxide-cyclic guanosine monophosphate cascade are currently the most promising compounds, but that none of these compounds is under investigation as a treatment option for systemic hypertension.